Cough as a clinical manifestation of large vessel vasculitis. Issue 3 (20th March 2022) - Azzam, Omar; Hubble, Daniel; Prentice, David
Abstract: Cough is not a widely recognised symptom of large vessel vasculitides. If not promptly diagnosed and treated, large vessel vasculitis can have serious clinical consequences. We present the case of a 76‐year‐old man who presented with a subacute history of persistent dry cough, was found to have extensive aortitis on imaging, and experienced rapid resolution of symptoms with immunosuppression.